2018
DOI: 10.3390/molecules23112806
|View full text |Cite
|
Sign up to set email alerts
|

Aloin Inhibits Müller Cells Swelling in a Rat Model of Thioacetamide-Induced Hepatic Retinopathy

Abstract: Swelling of retinal Müller cells is implicated in retinal edema and neuronal degeneration. Müller cell swelling is observed in patients with liver failure and is referred to as hepatic retinopathy. In the present study, we evaluated the effects of aloin, an anthraquinone-C-glycoside present in various Aloe species, on Müller cell dysfunction in a rat model of thioacetamide (TAA)-induced hepatic retinopathy. Experimental hepatic retinopathy was induced by three injections of TAA (200 mg/kg/day, intraperitoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…GFAP is upregulated during the light stress and blue light exposure, which leads to a nonspecific reactive change of Müller cells known as gliosis [ 55 , 56 ]. However, GFAP accumulation in Müller cells was reported as an essential photoreceptor stress parameter in retinopathy induced rats, in accordance with our findings [ 57 ]. In a recent study, a pattern of GFAP ADPase staining also suggested a robust Müller cells/astrocytes reactivity in the Goto-Kakizaki rat retina [ 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…GFAP is upregulated during the light stress and blue light exposure, which leads to a nonspecific reactive change of Müller cells known as gliosis [ 55 , 56 ]. However, GFAP accumulation in Müller cells was reported as an essential photoreceptor stress parameter in retinopathy induced rats, in accordance with our findings [ 57 ]. In a recent study, a pattern of GFAP ADPase staining also suggested a robust Müller cells/astrocytes reactivity in the Goto-Kakizaki rat retina [ 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…AL is one of the main active components in the leaf exudates of the Aloe vera plant, accounting for about 15%–40% [25]. An extensive literature review indicates that AL significantly increases the liver enzymes and improves the pathological changes in liver tissues in the models of chronic alcoholic liver injury [26] and thioacetamide- (TAA-) induced hepatic retinopathy [27]. Moreover, the protective effect of AL was documented before in I/R injury that occurred in the PC12 cells [28] and the heart [10, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al ( 91 ) observed in rat model of DR that after the application of the potassium channel opener pinadil, the expression of Kir4.1 was upregulated, the function of Müller cells was improved and the symptoms of retinal macular edema were alleviated. Another study suggested that aloe vera may help protect from retinal damage associated with liver failure by normalizing Kir4.1 and AQP4 through reducing oxidative stress and inflammation ( 92 ).…”
Section: Prospectsmentioning
confidence: 99%